Characterization of the S-locus region of almond (Prunus dulcis): analysis of a somaclonal mutant and a cosmid contig for an S haplotype. - Ushijima, K (2001)
Almond has a self-incompatibility system that is controlled by an S locus consisting of the S-RNase gene and an unidentified "pollen S gene." An almond cultivar "Jeffries," a somaclonal mutant of "Nonpareil" (S(c)S(d)), has a dysfunctional S(c) haplotype both in pistil and pollen. Immunoblot and genomic Southern blot analyses detected no S(c) haplotype-specific signal in Jeffries. Southern blot showed that Jeffries has an extra copy of the S(d) haplotype. These results indicate that at least two mutations had occurred to generate Jeffries: (1) deletion of the S(c) haplotype and (2) duplication of the S(d) haplotype. To analyze the extent of the deletion in Jeffries and gain insight into the physical limit of the S locus region, approximately 200 kbp of a cosmid contig for the S(c) haplotype was constructed. Genomic Southern blot analyses showed that the deletion in Jeffries extends beyond the region covered by the contig. Most cosmid end probes, except those near the S(c)-RNase gene, cross-hybridized with DNA fragments from different S haplotypes. This suggests that regions away from the S(c)-RNase gene can recombine between different S haplotypes, implying that the cosmid contig extends to the borders of the S locus.